The Growing Impact of Telemedicine in Modern Healthcare - Akram, Muhammad; Khan, Alam Afroz Urooj; Umaru, Isaac John; Shahid, Isbah (African Journal of Medicine, Surgery and Public Health Research, 2025)
Telemedicine employs technology to facilitate remote consultations and treatments, fundamentally changing healthcare practices. Its application increased significantly during the COVID-19 pandemic, enhancing healthcare access, reducing costs, and facilitating the management of chronic diseases and mental health issues. While offering distinct benefits, such as greater efficiency and enhanced accessibility, telemedicine also poses challenges, including technological hurdles, privacy issues, and legal restrictions. Emerging innovations such as artificial intelligence, smart gadgets, and interconnected health systems position telemedicine to become an essential element of contemporary healthcare. Targeted policy and infrastructure initiatives are crucial to promote equitable and effective use.